Potential of Rainwater System for Domestic Building in Jakarta. (May 2018) - Sari, Susy Prajna; Suhendri,
Abstract: Rainwater harvesting is the process of collecting, storing, and reusing rainwater. Different kinds of rainwater harvesting techniques have been used in developed and developing countries. Singapore, for instances, which has limited land sources and high demand of water, use rainwater harvesting technique on the high-rise buildings' roofs to get an alternative source of water. Also, in Japan, rainwater harvesting technique has been applied to residential areas and able to provide clean water for t oilet flushing, firefighter, and water supply in an emergency case. Nonetheless, rainwater management in Jakarta, compared to the countries mentioned above, is obviously left behind. With the high rainfall intensity, buildings in Jakarta are quietly possible to apply the rainwater harvesting technique. This paper is trying to analyse the potential of rainwater harvesting application in Jakarta. Starting from house buildings, the paper uses numerical calculation to study the environmental benefits of the rainwater harvesting implementation. The case study was taken in Gading Griya Residence, North Jakarta. The calculation results show that rainwater harvesting scheme can provide enough water supply for washing, flushing, fire extinguishing, and drinking water.